ANALISIS RENDEMEN TANDAN BUAH SAWIT BERDASARKAN TAHUN TANAM DAN VARIETAS DI PROVINSI RIAU - Azhari Rizal; Susilawardani; Hartini (Jurnal Agro Fabrica, 2022)
Palm oil (CPO) is extracted from loose palm fruit which is released from the oil palm fruit bunches, either naturally or by boiling. Several factors affect the yield of palm oil in the oil extraction process, including the year of planting and the variety planted. This study aims to look at the yield levels of oil palm fruit based on the variety year of planting so that the actual value is known and the effect of the year of planting on the yield value of FFB can be identified. The method used in this study refers to MPOB (Malaysia Palm Oil Board) and NRCOP (National Research Center of Oil Palm) standards which consist of 6 (six) stages, namely FFB sampling, initial calculation of FFB, seeds, and mesocarp, measuring moisture content, mesocarp oil extraction, calculating the percentage of kernels and shells, and calculating the value of the FFB material balance. Based on the results of the TB material balance analysis, it is known that the young planting year does not fully produce a low yield of palm oil, this is because many influencing factors cannot be controlled and are variables that cannot be locked/determined. The results of the average material balance for all planting years for the dry extraction method showed a CPO yield value of 22.97%, testing showed the highest yield was in the 2002 planted year with 27% content and the lowest was in the 2015 planted year with 19.68%.